Remote sensing of species dominance and the value for quantifying ecosystem services. Issue 3 (2nd August 2016) - Pau, Stephanie; Dee, Laura E.
Abstract : Remote sensing should play a pivotal role in monitoring Essential Biodiversity Variables (EBVs) across the globe, but this requires thoughtful consideration of how to connect remote sensing metrics with ecologically relevant variables. We argue that monitoring dominant species using remote sensing should be a priority because dominance is an ecologically relevant and scalable measure (of population abundance, community composition, trait representation and contribution to ecosystem function), can provide an early‐warning sign of ecological change, and overwhelmingly contributes to biomass‐driven ecosystem services (ESs). Furthermore, dominant species largely drive the satellite spectral signature. By identifying dominant species that disproportionately provide ESs, a new research direction for remote sensing is to address how ESs will change through time or across environmental gradients. This direction complements a growing body of work using remote sensing to map and quantify ESs. Abstract: Remote sensing (RS) is a powerful tool to measure and monitor Essential Biodiversity Variables (EBVs) and their environmental drivers. Despite this potential, stronger integration between remote sensing experts and the ecological community could better support biodiversity initiatives. Here we highlight opportunities to harness remote sensing technology to better understand biodiversity patterns, ecological processes and the consequences for ecosystem services (ESs). We argue that tracking many EBVs using remote sensing should prioritize the monitoring of dominant species, a scalable property across multiple EBV classes, for several reasons. First, a few dominant species in an ecological community disproportionately contribute to the satellite spectral signature. Second, a focus on dominance would enable a stronger links to ecological research, as dominance reflects the ecological community context (i.e. relative abundance of coexisting species). For example dominant species should be especially important contributors to many ecosystem functions and services that rely on abundance or biomass, such as carbon storage or nutrient cycling, because of their greater representation in a community. Furthermore, global change impacts on communities may be reflected in changing dominance structure before the losses of species, thus tracking dominance provides an early‐warning sign of community change for EBVs. Finally, focusing on dominant species should improve understanding of spatial and temporal dynamics of dominance‐driven ESs through RS mapping. Given the importance of dominant species to ecological communities and ESs, monitoring dominance under changing environmental conditions and human impacts should be a global priority.